The issues of a session in the Briefer Matrimonial Process before the Bishop - Bartczak, Adam (Prawo Kanoniczne, 2022)
The Briefer Matrimonial Process before the Bishop is characterized, inter alia, by the shortened evidentiary phase. For this purpose, the Legislator introduced the concept of a session. The meaning of the session has become the main concern of this article. In principle, it concerns the use of a specific term in Polish language. For this purpose, the author refers to various legal acts: Code of Canon Law (1917 and 1983), Instruction Provida Mater (1936), Instrutcion Dignitas connubii (2005), their comments and, finally, ratio legis of can. 1686 CIC. Uses methods characteristic of linguistic, systemic and functional interpretation. The analysis leads to the conclusion that the most frequently used term in Polish language does not fully reflect the meaning and function of the term session.